Explore Manila a feasibility study on the establishment of an online transportation guide for Metro Manila - Baltazar, Thea Mae Q.; Dormitorio, Dexter D.; Meteoro, Golda Meir L.; Riva, Phoebe J.
Tourists and ordinary citizens in Metro Manila find a hard time going to their destination, especiaiiy if they are not accustomed to the place yet. ExploreManila.ph is a commuters' guide for Metro Manila providing fast free access to all the necessary information needed by a commuter to travel from one piace to another in Metro Manila. The unique selling point of ExploreManila.ph is that the interface of the website is simple, clean and user-friendly. This website is primarily catered to internet - users, aged 15 and above that belongs to Class B,C,D,E. This can serve a over 50 Million web views in a year. The market has not been penetrated yet, thus, there is iow risk for competitors at this point. ExploreManila.ph will be in an excellent position by getting the right people, partnering with agencies, and deploying a concrete marketing plan to ensure market penetration. The web development involves analysis, building of specifications, design and development of the website, content writing, coding, testing, and maintenance and updating. The investment needed for the website to fully function and operate is approximately Php 4.9 Million. The business, however, can start up small for Php 320 000, and later expand. The revenue generation from advertisers for the website includes; week-long advertisement, year-long placement in map highlight, directory placement, and events page placement. These will have a projected annual revenue generation of Php 1,804,000 in the first year, Php 2,785,000 in the second year, Php 4,707,000 in the third year, Php 7,230,000 in the fourth year and Php 12,880,000 in the fifth year. The payback period for this investment is 3 years and has an IRR of 31%. Thus, this venture is attractive and profitable.